THREE‐DIMENSIONAL SEISMIC GEOMORPHOLOGY OF PALEOKARST IN THE CRETACEOUS MACAÉ GROUP CARBONATES, CAMPOS BASIN, BRAZIL. (26th September 2018) - Basso, M.; Kuroda, M. C.; Afonso, L. C. S.; Vidal, A. C.
Abstract : Three‐dimensional seismic data from an oilfield in the Campos Basin, SE Brazil, was used to characterize a karstified unconformity surface at the top of the Albian – Cenomanian Macaé Group. Macaé Group carbonates underwent intense karstification associated with subaerial exposure during a period of some 10 to 15 Ma resulting in the development of canyons, valleys, sinkholes and cave systems. The carbonates host commercial oil accumulations at a number of important oil fields. Understanding how the karstification process has affected the carbonates' reservoir properties is essential for future exploration, not only to improve recovery rates but also to avoid drilling‐related issues such as thief zones. In this context, this study aims to characterize the top‐Macaé Group paleokarst system by investigating the morphology of the associated reflectors recorded on seismic data, together with endokarst features in the underlying carbonate succession such as cave systems and collapse structures. The top‐Macaé Group seismic horizon can be divided into two principal geomorphological domains: highlands, characterized by abrupt relief with well‐developed erosional features; and lowlands, marked by a smoother topography. Collapse sinkholes occur in both domains and take the form of closed circular depressions. The study of endokarst features from an analysis of amplitude anomalies (bright spots) indicates the presence of heterogeneous cave systems. The interpreted data contributes to a better understanding of the spatial distribution of the paleokarst system in the Macaé Group carbonates and may assist with future hydrocarbon exploration in the Campos Basin.